Usted pregunta (Journal of Parents and Teachers, 2026)
Sometimes, decisions have to be made on the fly, worries plague us every day (and even every night) and suddenly circumstances that need to be resolved come to the fore, as in the cases in our section. How to solve the practical problem of the presence of television in our weekend property. How to dispel the anxiety that is triggered in an urgent and annoying way when it comes to choosing a costume for a Carnival party. On this occasion, we hear from different people in real life whom we consulted to get more information and make our decisions (or, at least, to put possible obsessions into perspective).
Keywords: television, rest, weekend, costume, carnival